RETRACTED: The Implementation of SILAS Values In School Quality Culture: A Phenomenological Study - Muh. Takdir; Dadan Samsul Badar; Tia Fajartriani (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2024)
RETRACTED: The editorial board of JPtpp has officially retracted the article "The Implementation of SILAS Values In School Quality Culture: A Phenomenological Study" (Vol.9, No.9, pp.388-397, September, 2024), due to a violation of publication ethics. Following a thorough review, the editor confirmed that this paper represents a duplicate publication. It contains redundant material previously published in JPtpp Vol.7, No.12, pp.648-656, December 2022, URL: https://journal.um.ac.id/index.php/jptpp/article/view/21326, under the title "The Implementation of SILAS Values in School Quality Culture: A Phenomenological Study". In accordance with institutional policies, the digital version of this document has been removed from previously published, and all citations or references to this paper should be discontinued. The aim of this study is to know the forms of the implementation of the values of silih asah (stimulating potential), silih asih (providing affection) and silih asuh (fulfilling the needs) well known as SILAS, namely the local genius values which are internalized in stakeholder activities to build school quality culture. This research used the qualitative approach from the phenomenology method. The participants were principals, teachers, staff and students of Junior High School at Purwakarta, Indonesia. The results of the study are; The value of silih asah is formed by self-capacity building through the training program and continuing studies to all teachers and staff, the students are involved actively in some academic and non-academic competitions, peer group learning, strong motivation from principal to all school citizenship to be competent and professional. The implementation of silih asih is formed by the sincerity of teachers and staff in serving the students learning needs, a harmonious relationship between the principal with teachers and staff, brotherhood and mutually protect between students, as well as the existence of a weekly program to repair the relationship between all of the school stakeholders in creating a friendly environment and social care. The value of silih asuh is formed by the student attitude, effective communication between principal with teachers and staff, teachers with staff, as well as by the principle 'right man on the right place' in carrying out the duties and responsibilities of all stakeholders professionally and proportionally. SILAS values become a school culture that is transformed in personal and organizational behaviours.